Extracellular factors and immunosuppressive drugs influencing insulin secretion of murine islets - Auer, V J (Blackwell Science Inc, 2012)
Approximately 60% of transplanted islets undergo apoptosis within the first week post-transplantation into the liver attributed to poor engraftment, immune rejection and toxicity of immunosuppressive drugs. Understanding how extracellular matrix (ECM) components, immunosuppressive drugs and proinflammatory cytokines affect insulin secretion will contribute to an improved clinical outcome of islet transplantations. In this study, functional activity of isolated murine islets was measured by glucose-stimulated insulin secretion (GSIS) and by electrophysiological measurements using patch-clamp. Cultivating islets with soluble fibronectin or laminin, as opposed to with coated laminin, markedly increased GSIS. Addition of cyclosporin A reduced GSIS and suppressed glucose-induced spike activity. Tacrolimus affected neither GSIS nor spike activity, indicating a different mechanism. To evaluate the influence of proinflammatory cytokines, islets were incubated with interleukin (IL)-1β, tumour necrosis factor (TNF)-α or with supernatants from cultured Kupffer cells, the main mediators of inflammation in the hepatic sinusoids. IL-1β exerted a bimodal effect on insulin secretion, stimulating below 2 ng/ml and suppressing above 10 ng/ml. Soluble laminin in combination with a stimulatory IL-1β concentration further increased insulin secretion by 20% compared to IL-1β alone, while with high IL-1β concentrations soluble laminin slightly attenuated GSIS inhibition. TNF-α alone did not affect GSIS, but with stimulatory IL-1β concentrations completely abolished it. Similarly, supernatants derived from Kupffer cells exerted a bimodal effect on GSIS. Our data suggest that improved insulin secretion of transplanted islets could be achieved by including soluble laminin and low IL-1β concentrations in the islet cultivation medium, and by a simultaneous inhibition of cytokine secretion from Kupffer cells.